Oral Health Status of Health Care Workers in Tertiary Care Hospitals of Rawalpindi, Islamabad Pakistan: Oral Health Status of Health Care Workers - Farrukh Habib, Muhammad; Pervaiz, Ayesha; Riaz, Hassan; Mahmood, Humaira; Khan, Jawaria; Raisani, Sher Afgan; Kakakhel, Syed Ihtishaam; Riaz, Nimra (Pakistan Journal of Health Sciences, 2023)
Studies from all around the world have shown that healthcare professionals may encounter a number of obstacles to receiving dental care, which raises the prevalence of oral disorders in this population. In recent years, Pakistan has not done a national oral health assessment on the state of oral health among healthcare workers. Objective: To determine the oral health status of health care workers in tertiary care hospitals using Decayed, Missed, Filled tooth Index. Methods: Descriptive cross-sectional study was conducted utilizing a simple random selection and 385 healthcare workers between the ages of 20-50 years. Healthcare workers were assessed in tertiary care hospitals, and information on caries and gingival health was gathered. For the oral examination, the standards and procedures of the WHO were applied. Results: Only 9.8% of the respondents were healthy and mean DMFT score came out to be 3.28 ± 1.12. Conclusions: Healthcare workers in tertiary have unsatisfactory dental practices, poor attitude related to oral health and general lack of awareness about oral health.